Support Patterns of Roadways Under Fractured Surrounding Rocks Based on the Quality Level of Rock Mass - Chi Ma; Peitao Wang; Jiajun Li; Xingwang Fan; Zhihong Dong; Ziming Chen; Xingwu Wang (Applied Sciences)
The roadway project of broken rock mass in the Shilu Iron Deposit was taken as the research object to discuss the stability control of the surrounding rocks using support patterns with broken rock mass. The grade evaluation of rock mass quality was conducted based on the geomechanical classification of rock mass. The roadway support effect in broken rock mass was calculated. Then, the section convergence characteristics of roadway surrounding rocks were analyzed under the current support scheme using displacement monitoring technology. The conclusions were described as follows: (1) The surrounding rock integrity of the No.6 and No.7 transportation roadways in the middle section of the Baoxiu mining area (Level 120) is poor. Based on geological survey data and rock mass classification, the rock mass quality in this region has been rated as Class IV. The joint support pattern of the anchor net and shotcrete was used according to the support guidelines. (2) The parameters for the support structure within Shilu Iron Deposit were designed, according to the requirements, as follows: the use of Portland cement; a shotcrete thickness of 55 mm; resin bolts with a minimum outer diameter of φ 20 mm and a length of 2200 mm; and row and column spacings of 1100 mm each. Meanwhile, a rectangular metal mesh of 80 × 80 mm was used as the anchor mesh. (3) The cross-section displacement reached 20 mm within a week using the support pattern according to displacement monitoring results of the on-site roadway section. Moreover, the convergence deformation rate significantly changed. However, the rate rapidly decreased after the first week, and the cross-section showed no further deformation after one month. The support pattern could control the displacement of surrounding rocks, which was verified by the monitoring results.